Security and privacy protection in information processing systems : 28th IFIP TC 11 International Conference, SEC 2013, Auckland, New Zealand, July 8-10, 2013. Proceedings - Wolfe, Henry B.; Shenoi, Sujeet; Janczewski, Lech J. (IFIP Advances in Information and Communication Technology, 2013)
This book constitutes the refereed proceedings of the 28th IFIP TC 11 International Information Security and Privacy Conference, SEC 2013, held in Auckland, New Zealand, in July 2013. The 31 revised full papers presented were carefully reviewed and selected from 83 submissions. The papers are organized in topical sections on malware, authentication and authorization, network security/cryptography, software security, policy compliance and obligations, privacy protection, risk analysis and security metrics, social engineering, and security management/forensics.